The representation of public opinion in reporting poll results on environment issues - Nagai, Kentaro (Frontiers in Communication, 2023)
This study examines how Japanese newspapers reporting the results of public opinion polls represent a unified picture of public opinion on environmental issues. Focusing on public opinion poll coverage, we argue that certain results are emphasized to the exclusion of others. To this end, this study analyzes articles and headlines of public opinion poll results on environmental issues published by three Japanese newspapers, the Asahi newspaper, the Yomiuri newspaper, and the Mainichi newspaper, from 1988 to 2010. In total, we located 64 articles that contain 179 headlines and subheadings. Findings suggest that the news coverage most often emphasized people's fears and concerns about environmental issues, followed by individuals' willingness to adopt environmentally friendly behaviors and practices, such as energy conservation and recycling. Overall, the headlines tend to give the impression that many respondents support this view. However, some media outlets that follow this trend selectively emphasize only one aspect of the poll results in their headlines without pointing out the existence of a conflict. They interpret poll results using second person or collective nouns to indicate the distribution of opinions. They then imply an overarching, unified public opinion that indicates a certain direction. This paper concludes that media representations of public opinion based on the results of Japanese public opinion polls on environmental issues legitimize existing political and economic structures and attribute responsibility for environmental problems to individuals.